2020
DOI: 10.1021/acssynbio.0c00256
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Free Protein Expression System Derived from Human Primary Peripheral Blood Mononuclear Cells

Abstract: Historically, some of the first cell-free protein expression systems studied in vitro translation in various human blood cells. However, because of limited knowledge of eukaryotic translation and the advancement of cell line development, interest in these systems decreased. Eukaryotic translation is a complex system of factors that contribute to the overall translation of mRNA to produce proteins. The intracellular translateome of a cell can be modified by various factors and disease states, but it is impossib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Numerous experiments and techniques facilitate exploring endogenous and exogenous expression of micropeptides. Detecting exogenous expression primarily relies on designing vectors and transfecting target genes, immunofluorescence, immunoprecipitation, and cell‐free protein expression system 94 . Also, generating target antibody and CRISPR/Cas9 knock‐in TAG are used to detect endogenous expression 28 .…”
Section: Methods and Technologies For Predicting And Characterizing S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experiments and techniques facilitate exploring endogenous and exogenous expression of micropeptides. Detecting exogenous expression primarily relies on designing vectors and transfecting target genes, immunofluorescence, immunoprecipitation, and cell‐free protein expression system 94 . Also, generating target antibody and CRISPR/Cas9 knock‐in TAG are used to detect endogenous expression 28 .…”
Section: Methods and Technologies For Predicting And Characterizing S...mentioning
confidence: 99%
“…Detecting exogenous expression primarily relies on designing vectors and transfecting target genes, immunofluorescence, immunoprecipitation, and cell-free protein expression system. 94 Also, generating target antibody and CRISPR/Cas9 knock-in TAG are used to detect endogenous expression. 28 Given the continuous in-depth research, it is found that micropeptides function in transcription regulation, DDR, translation regulation, mitochondria fission, and so on.…”
Section: Micropeptides Localized In the Nucleusmentioning
confidence: 99%